Digital Marketing: Pengaruh Konten Promosi Pariwisata Terhadap Kepuasan Wisatawan Dan Loyalitas Wisatawan: Indonesia - Sulkaisi, Neffi; Emely, Bamy; Saputra, Syailendra Eka; Kemalasari, Mareta; Selvia, Nisha (CV. ITTC INDONESIA, 2023)
This research explores the influence of promotional content variables, tourist satisfaction and tourist loyalty. The collection technique uses nonprobability sampling with incidental sampling. This research involved 300 tourists who visited Mentawai Tourism, then analyzed using the SEM method. The research results show that there is a direct influence between the content promotion variable on tourist satisfaction and tourist loyalty as well as an indirect influence between content promotion on tourist loyalty through the tourist satisfaction variable..